2008
DOI: 10.1364/ol.33.001324
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized probe based on a microelectromechanical system mirror for multiphoton microscopy

Abstract: A factor that limits the use of multiphoton microscopy (MPM) in clinical and preclinical studies is the lack of a compact and flexible probe. We report on a miniaturized MPM probe employing a microelectromechanical system (MEMS) scanning mirror and a double-clad photonic crystal fiber (DCPCF). The use of a MEMS mirror and a DCPCF provides many advantages, such as size reduction, rapid and precise scanning, efficient delivery of short pulses, and high collection efficiency of fluorescent signals. The completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 12 publications
(18 reference statements)
1
61
0
Order By: Relevance
“…The development of NLOM probe based on multiphoton excitation that uses a near infrared laser beam for imaging is in progress by several groups [20][21][22]. An important factor that limits the use of NLOM probe in clinical studies is the lack of a compactness and flexibility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of NLOM probe based on multiphoton excitation that uses a near infrared laser beam for imaging is in progress by several groups [20][21][22]. An important factor that limits the use of NLOM probe in clinical studies is the lack of a compactness and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…An important factor that limits the use of NLOM probe in clinical studies is the lack of a compactness and flexibility. Jung et al, reported a miniaturized multiphoton microscopy probe that was developed by employing a microelectromechanical system scanning mirror and a double-clad photonic crystal fiber [20]. The size of probe head was 1 cm in outer diameter and 14 cm in length [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compact circuit board is designed by AdvancedMEMS, Inc. to guarantee a miniaturized probe with the ability to image tissue in vivo [40,41]. V grooves included in the probe can help to adjust the positional tolerance in XYZ decenter, Theta, and Phi-tilt of both the MEMS device and collimator component.…”
Section: Multimodal Nonlinear Endo-microscopy Probe Schemementioning
confidence: 99%
“…Recent advances in this direction include development of fiber-based compact probes which are being used successfully in optical imaging techniques based on optical coherence tomography 1 , two-photon fluorescence (TPEF) and second harmonic generation (SHG) 2,3 . Among the optical imaging methods currently used, the development of coherent anti-Stokes Raman Scattering (CARS) remains at a level much closer to the laboratory bench than to the clinic.…”
Section: Introductionmentioning
confidence: 99%